Study of Glucosamine Production from Shrimp Shells by Fermentation Using Trichoderma harzianum - Hardoko, Hardoko; Sasmito, Bambang B.; Puspitasari, Yunita E.; Afandi, Hamid M.; Maulia, Nugroho (The Journal of Experimental Life Science, 2017)
Shrimp shells are one of chitin sources in Indonesia which is potential to be converted into multifunctional glucosamine. This research was aimed to study the glucosamine production by fermentation using Trichoderma harzianum.Â  Method used was experimental fermentation with pH treatment of 3-5 and fermentation duration of 10-20 days, and designed using Response Surface Methodology (RSM). Results showed that fermentation duration of 10-20 days has reached the optimum point of glucosamine production from shrimp shells using T. harzianum. The highest production of D-glucosamine in fermentation using T. harzianum occurred on initial pH of 5.41 and fermentation duration of 15 days (18,294.95 ppm), while the highest N-Acethyl-D-Glucosamine production occurred on initial pH of 3.00 and fermentation duration of 20 days (127,000.00 ppm).Keywords: fermentation, glucosamine, shrimp shells, T. harzianum.